2019
DOI: 10.1371/journal.pone.0214060
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-C1-C4-C2 gene cluster region and inter-individual variation in plasma lipoprotein levels: a comprehensive genetic association study in two ethnic groups

Abstract: The apolipoprotein E-C1-C4-C2 gene cluster at 19q13.32 encodes four amphipathic apolipoproteins. The influence of APOE common polymorphisms on plasma lipid/lipoprotein profile, especially on LDL-related traits, is well recognized; however, little is known about the role of other genes/variants in this gene cluster. In this study, we evaluated the role of common and uncommon/rare genetic variation in this gene region on inter-individual variation in plasma lipoprotein levels in non-Hispanic Whites (NHWs) and Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…Recent advances in research demonstrated that long non-coding RNA is endowed with regulatory properties, as reviewed in [25]. In this respect, a recent report identified polymorphism rs5112 in APOC1P to significantly affect LDL-cholesterol levels in non-Hispanic Whites [16]. In addition, non-coding RNA APOC1P1-3 was found to reduce α-tubulin acetylation and consequently block apoptosis in breast cancer [26] and to regulate migration and inflammation in cholangiocarcinoma [27].…”
Section: Apoc1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in research demonstrated that long non-coding RNA is endowed with regulatory properties, as reviewed in [25]. In this respect, a recent report identified polymorphism rs5112 in APOC1P to significantly affect LDL-cholesterol levels in non-Hispanic Whites [16]. In addition, non-coding RNA APOC1P1-3 was found to reduce α-tubulin acetylation and consequently block apoptosis in breast cancer [26] and to regulate migration and inflammation in cholangiocarcinoma [27].…”
Section: Apoc1 Genementioning
confidence: 99%
“…Although the three APOE alleles appear to be determinant for the plasma lipidemia [15], other apoE-independent polymorphisms found in the cluster contribute to lipid homeostasis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In each simulation, we randomly selected 2 or 7 of variants generated from the CEU 1000 Genomes reference as causal variants; None of the variants generated from the YRI 1000 Genomes reference samples was selected as causal, mimicking the genetic heterogeneity observed in Pirim et al (2019). Out of K = 10 studies, we considered 1, 2, 5, or 7 studies composed of the CEU samples, and the rest were YRI samples.…”
Section: Simulationsmentioning
confidence: 99%
“…The simulated CEU samples included 15 RVs in the APOE region, while the simulated YRI samples included 30 RVs. In each simulation, we randomly selected 2 or 7 of variants generated from the CEU 1000 Genomes reference as causal variants; None of the variants generated from the YRI 1000 Genomes reference samples was selected as causal, mimicking the genetic heterogeneity observed in Pirim et al (2019).…”
Section: Simulationsmentioning
confidence: 99%
“…In the Finnish cohort, the 19q13.31 and 19q13.32 loci exhibited genome-wide significance for serum LDL concentration, but the 1p32 loci did not [ 15 ]. On the other hand, the loci were reported to be associated with TG and HDL in non-Hispanic Caucasians and Africans [ 16 ]. These studies indicate that the genetic variants in 19q13.32 play an important role in the lipid metabolism, including hyper-LDL-cholesterolemia.…”
Section: Introductionmentioning
confidence: 99%